Water Vapor Changes Affect Cross-Seasonal Strong Drought Events in the Eastern Region of Northwest China - Zhang, Yu; Liu, Kang; Li, Yaohui; Shen, Wei; Ren, Yulong; Zeng, Dingwen; Sha, Sha (Frontiers in Earth Science, 2021)
Drought in eastern Northwest China (ENC) is severely affected by water vapor conditions. An in-depth study of the primary sources of water vapor and its characteristics, at intraseasonal and interannual timescales, was conducted. This information is crucial for further study of the causes and mechanisms of extreme droughts and floods in the ENC. This study evaluated the spatial distribution and transport characteristics of water vapor over ENC during the 1981–2019 period based on the fifth generation of the European Center for Medium-Range Weather Forecasts atmospheric reanalyzes data of the global climate (ERA5). We studied the water vapor transport routes, water vapor convergence, water vapor budgets as well as the changes in water vapor fluxes and budgets over time in four areas surrounding ENC. The Mediterranean Sea, Black Sea, Caspian Sea, Indian Ocean, Bay of Bengal, and the South China Sea were the main sources of water vapor in ENC, supplemented by mid to high-latitude continental sources. The monthly change in water vapor flux in ENC exhibited the peak on July. The transport of water vapor in ENC was mainly toward the east and north. For most cross-seasonal drought events, the water vapor output is the main way in the south boundary and the west boundary. However, for the longest duration of cross-seasonal strong drought events, it is characterized by that the water vapor output is the main way in the south boundary, while the water vapor input in the north boundary is obviously weak. Water vapor paths in cross-seasonal strong drought events are analyzed, by which the Hybrid Single-Particle Lagrangian Integrated Trajectory model (HYSPLIT). The intensity of the subtropical high in the western Pacific is weak and the position is south, which corresponds to the occurrence of cross-seasonal strong drought in the ENC.